(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
The current study deals with fabricating a hybrid nanocomposite. Pure aluminum as the base matrix and Fe2O3 and Al2O3. A reinforcements Fe2O3 weight percentage (wt%) is varied (1.5, 2.5 and 5 % wt%) and Al2O3 is held constant (2 wt%). The new designed nanocomposite was produced using Powder Metallurgy (P/M) method. The experimental results revealed that the microstructure images of nanocomposites showed uniformly distributed of Fe2O3 and Al2O3 in aluminum matrix. Dry tribological behavior (wear rate and coefficient of friction) was studied and for varying hybrid reinforcement content. The results observed that the wear resistance of hybrid nanocomposites improved with the increasing of Fe2O3 + Al2O3 reinforced material but the better wear resistance was recorded with the (1.5% Fe2O3 + 2% Al2O3) wt% than the base metal and other nanocomposites. It is evident that the maximum reduction of wear rate and COF were 4.87 × 10-8 g/m and 0.59 respectively for the (1.5% Fe2O3 + 2% Al2O3) nanocomposite. The hysteresis curve of nanocomposites showed that the magnetic properties which indicated that the better response of magnetic properties was found with the nanocomposite of (1.5% Fe2O3 + 2% Al2O3) content.